Investigation on sexual function in young breast cancer patients during endocrine therapy: a latent class analysis - Gan, Lu; Miao, Yi-Ming; Dong, Xiao-Jing; Zhang, Qi-Rong; Ren, Qing; Zhang, Nan (Frontiers in Medicine, 2023)
The aim of this study was to investigate the sexual function status of young breast cancer patients during endocrine therapy, identify potential categories of sexual function status, and analyze the factors affecting the potential categories of sexual function status during endocrine therapy. Methods: A cross-sectional survey was conducted on 189 young breast cancer patients who underwent postoperative adjuvant endocrine therapy in Shanghai Ruijin Hospital. The latent class analysis was used to identify potential categories of patient sexual function characteristics with respect to the FSFI sex health measures. Logistic regression analysis was used to analyze the influencing factors for the high risk latent class groups. A nomogram prognostic model were then established to identify high risk patients for female sexual dysfunction (FSD), and C-index was used to determine the prognostic accuracy. Results: Patients were divided into a "high dysfunction-low satisfaction" group and a "low dysfunction-high satisfaction" group depending on the latent class analysis, accounting for 69.3% and 30.7%, respectively. Patients who received AI(Aromatase inhibitors) combined with OFS(Ovarian Function Suppression) treatment (P=0.027), had poor body-image after surgery (P=0.007), beared heavy medical economy burden(P<0.001), and had a delayed recovery of sexual function after surgery (P=0.001) were more likely to be classified into the "high dysfunction-low satisfaction" group, and then conducted into the nomogram. The C-index value of the nomogram for predicting FSD was 0.782 .The study revealed the heterogeneity of sexual function status among young breast cancer patients during endocrine therapy, which may help identify high-risk patients and provide early intervention.